In vitro antimalarial activity of essential oils of Deverra scoparia Coss. & Dur | JBES - Hammoudi, Roukia; Sanon, Soulaymene; Mahammed, Mahfoud, Hadj (My University, 2022)
The essential oils of the plant Deverra scoparia Coss. & Dur. (Apiaceae) used in traditional medicine in Algeria were subjected to testing the antimalarial activity. Their potential ability to inhibit the in vitro proliferation was evaluated in two strains of Plasmodium falciparum; chloroquine-resistant (K1), and chloroquine-sensitive (3d7) strains. The essential oils displayed good antimalarial activity with IC50 values 1.51 ± 0.71 μg/mL and 0.93 ± 0.89 μg/mL against the 3d7 chloroquine-sensitive and the K1 chloroquine-resistantstrains respectively. So, Deverra scoparia presented a potential source of antimalarial molecules.
Supplemental Materials: https://osf.io/yzev9/
Keywords: Antimalarial; Activity; Essential oil; Deverra scoparia; Apiaceae; jbes